Cell Death Mechanisms Induced by Photo-Oxidation Studied at the Cell Scale in the Yeast Saccharomyces cerevisiae - Grangeteau, Cédric; Lepinois, Florine; Winckler, Pascale; Perrier-Cornet, Jean-Marie; Dupont, Sebastien; Beney, Laurent (Frontiers in Microbiology, 2018)
Blue light (400-430 nm) is known to induce lethal effects in some species of fungi by photo-oxidation caused by the excitation of porphyrins but the mechanisms involved remain poorly understood. In this work, we exposed the yeast Saccharomyces cerevisiae to a high density light flux with two-photon excitation (830 nm equivalent to a one-photon excitation around 415nm) and used quasi real-time visualization with confocal microscopy to study the initiation and dynamics of photo-oxidation in subcellular structures. Our results show that the oxidation generated by light treatments led to the permeabilization of the plasma membrane accompanied by the sudden expulsion of the cellular content, corresponding to cell death by necrosis. Moreover, excitation in the plasma membrane led to very fast oxidation and membrane permeabilization (less than 60 seconds) while excitation at the center of the cell did not induce permeabilization even after a period exceeding 600 seconds. Finally, our study shows that the relationship between the laser power used for two-photon excitation and the time required to permeabilize the plasma membrane was not linear. Thus, the higher the power used, the lower the energy required to permeabilize the plasma membrane. We conclude that fungal destruction can be generated very quickly using a high density light flux. Better knowledge of the intracellular processes and the conditions necessary to induce necrosis should make it possible in the future to improve the efficiency of antimicrobial strategies photo-oxidation-based.